STEM-robotic: Meningkatkan kompetensi guru dalam mengimplementasikan STEM dan pengodean (coding) - Falenthino Sampouw; Andi Fajeriani Wyrasti; Faisal Faisal; Irfan Irnandi; Benidiktus Tanujaya; Jeinne Mumu; Maryo Sopater Istia; Haryanto Haryanto; Riris Indarwati; Sisilia Almandha; Dewi Brilliana Putri (Universitas Pendidikan Indonesia, 2026)
The STEM-Robotics training at YPPK St. Thomas Aquino Junior High School in Kaimana, West Papua, was conducted to address teachers' low understanding of STEM and coding concepts and the suboptimal utilization of robotics facilities in schools. This program aims to improve teachers' understanding of STEM learning, coding competency, and attitudes toward the implementation of STEM-Coding. The program was implemented using a service-learning approach involving 28 teachers, 4 lecturers, and 3 students across five stages: needs identification, collaborative planning, practice-based implementation, critical reflection, and evaluation. Data were collected using a validated questionnaire and analyzed descriptively. The training results showed that teachers' understanding of STEM learning reached 52% in the moderate category and 48% in the high category. Teachers' understanding of coding reached 4% in the moderate category and 96% in the high category. In comparison, positive attitudes toward STEM-Coding learning reached 11% in the moderate category and 89% in the high category. Overall, all program success indicators were met, with more than 85% of teachers in the moderate-to-high category across all measured aspects. This program is effective in improving teacher competency and supporting the development of technology-based learning in areas with limited access to education.